2021
DOI: 10.1371/journal.pone.0248914
|View full text |Cite
|
Sign up to set email alerts
|

Community participation in the collaborative governance of primary health care facilities, Uasin Gishu County, Kenya

Abstract: Introduction Community participation in the governance of health services is an important component in engaging stakeholders (patients, public and partners) in decision-making and related activities in health care. Community participation is assumed to contribute to quality improvement and goal attainment but remains elusive. We examined the implementation of community participation, through collaborative governance in primary health care facilities in Uasin Gishu County, Western Kenya, under the policy of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Building relationships based on mutual trust and meaningful exchange of ideas and information were reported to be of particular importance for marginalised groups [ 12 , 54 , 56 , 86 ]. Studies also highlighted that the encounter between PHC providers and community requires cultural competence–the ability of providers to translate information in a way that gives due consideration to health literacy level and encourages community understanding [ 44 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building relationships based on mutual trust and meaningful exchange of ideas and information were reported to be of particular importance for marginalised groups [ 12 , 54 , 56 , 86 ]. Studies also highlighted that the encounter between PHC providers and community requires cultural competence–the ability of providers to translate information in a way that gives due consideration to health literacy level and encourages community understanding [ 44 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Building relationships based on mutual trust and meaningful exchange of ideas and information were reported to be of particular importance for marginalised groups [ 12 , 54 , 56 , 86 ]. Studies also highlighted that the encounter between PHC providers and community requires cultural competence–the ability of providers to translate information in a way that gives due consideration to health literacy level and encourages community understanding [ 44 , 54 ]. Several reviews included in our study reiterated that for CE activities to be meaningful and lead to positive change for communities, they need to be based on transparency, trust-building and information-sharing between communities and service providers, as this will enable people to feel comfortable seeking PHC services while providing PHCs with the opportunity to align services to community’s need.…”
Section: Resultsmentioning
confidence: 99%
“…The governance of the primary health care facilities is significantly needed now than ever because of the decisions that HFGCs have to make to combat COVID 19. Since primary health facilities can not be depending on decisions made by the top officially upper levels [41], HFGCs are advantageous to make contextual-based and timely decisions and institute relevant governance strategies that can minimize the COVID 19 effects at the subnational level. Strengthened governance institutions such as HFGCs promise for effective governance of COVID 19 and other pandemics in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 One study in Tanzania showed that community members did not know about community-level committees, which hindered their functionality. 35 There is literature on facility-based HFMCs in Kenya, 22,36,37 but literature on community health structures for overseeing community health services in limited. 38 This research aimed to contribute to the body of knowledge on community participation by examining how contextual factors influence the functionality of CHCs in diverse ecological settings in Kenya.…”
Section: Community Participation and Community-level Health Committee...mentioning
confidence: 99%